2017
DOI: 10.1149/2.0551706jes
|View full text |Cite
|
Sign up to set email alerts
|

On The Corrosion and Metastable Pitting Characteristics of 316L Stainless Steel Produced by Selective Laser Melting

Abstract: The austenitic stainless steel 316L was additively manufactured using Selective Laser Melting (SLM). The corrosion characteristics of the additively manufactured (3D printed) specimens were investigated by both potentiodynamic and potentiostatic techniques. The production parameters were deliberately varied during SLM, to produce 316L specimens fabricated by different laser scan speed (in the range of 860-1160 mm/s) and laser power (in the range of 165-285 W). The fabrication parameters were found to influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

22
139
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(164 citation statements)
references
References 35 publications
(57 reference statements)
22
139
2
1
Order By: Relevance
“…The corrosion behaviour has been systematically investigated as a function of the main laser parameters (laser power and scan speed), which mainly determine the amount and size of pores in the material. For materials containing pores with a size larger than 10 µm, it is reported that the porosity does not significantly affect the breakdown of passivity (E pit ) in potentiodynamic polarization curves, while it has a more relevant effect on metastable pitting and on the repassivation behaviour of SLM 316L stainless steel . Materials obtained with scan speeds in the range of 1,000–1,400 mm/s tend to display a higher density of pits, that were associated to the presence of pores with increasing size and number, although the pitting potential was only slightly affected by the variation of the scan speed …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The corrosion behaviour has been systematically investigated as a function of the main laser parameters (laser power and scan speed), which mainly determine the amount and size of pores in the material. For materials containing pores with a size larger than 10 µm, it is reported that the porosity does not significantly affect the breakdown of passivity (E pit ) in potentiodynamic polarization curves, while it has a more relevant effect on metastable pitting and on the repassivation behaviour of SLM 316L stainless steel . Materials obtained with scan speeds in the range of 1,000–1,400 mm/s tend to display a higher density of pits, that were associated to the presence of pores with increasing size and number, although the pitting potential was only slightly affected by the variation of the scan speed …”
Section: Introductionmentioning
confidence: 99%
“…The size of the particles ranges between few nanometers up to 1 µm . MnS inclusions are typically not found in SLM 316L stainless steel . The formation of an intragranular cellular structure in combination with randomly distributed nanoinclusions improves the mechanical properties of SLM 316L stainless steel …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the SLM 316L also displayed increased pitting frequency and decreased repassivation potentials related to increasing specimen porosity. 20 The non-equilibrium nature of rapid solidification during the SLM process can lead to cellular-dendritic solidification substructures with locally heterogeneous compositions. [21][22][23] The comparatively Cr-lean cellular regions could have compromised passive oxide continuity relative to the surrounding cell boundaries and initiated preferential corrosion attack in chloride solutions.…”
mentioning
confidence: 99%